Determination of metallic content in various components in waste PCB for recycling via hydrometallurgical process - Kasogi, Abraham Nathanael (Nanyang Technological University, 2020)
The number of waste PCB is growing exponentially every year due to the advancement of technology and the shorter lifespan of electronic products. In this research, the metallic contents of eight electrical components from waste PCB are determined. Major metals detected in this research are Cu, Al, Au, Ag, Sn, Ta, Pb. An environmentally friendly recycling method is designed and proposed for each of the components in WPCB. This research provides a basis for further study and research in optimizing the environmentally friendly recycling process for each of the components in the waste PCB.